Tumor Necrosis Factor-Alpha Gene Promoter Region Polymorphism and the Risk of Coronary Heart Disease - Gul Zareen Asifa; Afrose Liaquat; Iram Murtaza; Syed Ali Raza Kazmi; Qamar Javed (The Scientific World Journal)
Background. Tumor necrosis factor-alpha (TNF-α) gene polymorphisms have been implicated in the manifestation of atherosclerosis. Controversy exists regarding the link between the cytokine’s variant genotype and CHD among different ethnic groups. There have been fewer studies on the TNF-α gene −1031T>C and −863C>A polymorphisms in relation to CHD. Therefore, the current study was designed to investigate the association of the TNF-α gene −1031T>C and −863C>A polymorphisms with CHD in a Pakistani population. Methods. Patients with CHD (n=310) and healthy individuals (n=310) were enrolled in this study. Genotyping was performed by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). Results. A significant difference was observed in the −863C>A polymorphism between patients with CHD and control subjects (P<0.0001). CHD risk was positively associated with the variant allele −863A (P<0.0001) in the study subjects. There was no significant link between the −1031T>C polymorphism and CHD risk in the study population. Haplotypes A-T and A-C of the TNF-alpha gene loci at −863 and −1031 showed higher frequency in the patient group compared with controls (P<0.05). Conclusion. The TNF-α  −863C>A gene polymorphism was associated with the pathogenesis of CHD while the −1031T>C polymorphism did not show any link with the disease in a Pakistani population.